Perlindungan Hukum Pemegang Hak Cipta Terhadap Pembajakan Potongan Film Pada Aplikasi Tiktok - I Gusti Ayu Eviani Yuliantari; I Gede Agus Kurniawan; Ni Putu Dian Puspita Dewi (Jurnal Hukum Sasana, 2023)
Film piracy has now penetrated into the TikTok application. The need for protection of copyright holders against acts of copyright infringement, especially film piracy. This explanation creates a formulation of the problem, namely how to regulate the law regarding film piracy in the laws and regulations in Indonesia and how is the legal protection of copyright holders against piracy of film clips on the TikTok application. This writing uses a type of normative research with statutory research approaches and conceptual research approaches. This writing relates to the principle of protection, the principle of legal certainty, and the principle of lex specialis derogate legi generalis. In addition to using the theory of legal protection and theory of intellectual property rights. The results of this study are that the regulations governing film piracy are contained in the Copyright Law and the Film Law, however, piracy of film clips on the TikTok application uses the Copyright Law. Compared to the Film Act which only regulates film piracy on films without passing censorship. The form of protection for copyright holders is included in the film on the TikTok application in the form of preventive and repressive protection.